Backbone Engineering within a Latent β-Hairpin Structure to Design Inhibitors of Polyglutamine Amyloid Formation. Issue 2 (20th January 2017) - Kar, Karunakar; Baker, Matthew A.; Lengyel, George A.; Hoop, Cody L.; Kodali, Ravindra; Byeon, In-Ja; Horne, W. Seth; van der Wel, Patrick C.A.; Wetzel, Ronald
Abstract: Candidates for the toxic molecular species in the expanded polyglutamine (polyQ) repeat diseases range from various types of aggregates to "misfolded" monomers. One way to vet these candidates is to develop mutants that restrict conformational landscapes. Previously, we inserted two self-complementary β-hairpin enhancing motifs into a short polyQ sequence to generate a mutant, here called "βHP, " that exhibits greatly improved amyloid nucleation without measurably enhancing β-structure in the monomer ensemble. We extend these studies here by introducing single-backbone H-bond impairing modifications α N -methyl Gln orl -Pro at key positions within βHP. Modifications predicted to allow formation of a fully H-bonded β-hairpin at the fibril edge while interfering with H-bonding to the next incoming monomer exhibit poor amyloid formation and act as potent inhibitors in trans of simple polyQ peptide aggregation. In contrast, a modification that disrupts intra -β-hairpin H-bonding within βHP, while also aggregating poorly, is ineffective at inhibiting amyloid formation in trans . The inhibitors constitute a dynamic version of the edge-protection negative design strategy used in protein evolution to limit unwanted protein aggregation. Our data support a model in which polyQ peptides containing strong β-hairpin encouraging motifs only rarely form β-hairpin conformations in the monomer ensemble, but nonetheless take on such conformations at key steps during amyloid formation. The results provide insights into polyQ solution structure and fibril formation while also suggesting an approach to the design of inhibitors of polyQ amyloid growth that focuses on conformational requirements for fibril and nucleus elongation. Graphical Abstract: Highlights: β-Hairpin formation is implicated in polyQ amyloid nucleation and structure. We prepared polyQ peptides combining β-hairpin motifs with backbone modifications. Peptides with α N-Me-Gln or Pro mutations in the predicted hairpin aggregate poorly. Such mutations at predicted non-H-bonding positions inhibit aggregation in trans . The data clarify assembly mechanisms and provide valuable tools for disease studies.